APPLICATION OF SWOT ANALYSIS AND MILKSFISH TRADING STRATEGY IN INDONESIA - Rahmah, Hatma Aura (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2022)
Milkfish is the leading fishery commodity in Indonesia, so there are many people who clear land for milkfish cultivation. Milkfish has a specialty because of its high nutritional and nutritional content. In the national fishery sector, aquaculture plays an important role with the average national milkfish consumption level of 1.40 kg/capita with market absorption at the household level of 352,718 tons. In milkfish cultivation, various preparations and good considerations are needed. SWOT analysis is the right method to see the development of aquaculture trade in Indonesia. through SWOT analysis is able to provide the concept of strategic planning on the results of the analysis of the company's strategic factors (strengths, weaknesses, opportunities and threats). With the strategy, the trade system will facilitate mobilization activities to facilitate channels and can provide more satisfaction to consumers. However, in marketing fishery products, various specific problems are faced because they are caused by the characteristics of fishery commodities. Therefore, a sustainable marketing strategy is needed to improve the economy and welfare for them.